Literasi numerasi anak sekolah dasar dan kontribusi orang tua dalam lingkungan keluarga - Karimah, Indah Uzlifatul (Maliki Interdisciplinary Journal, 2026)
Numeracy literacy is a fundamental competence that supports the mastery of basic mathemathical concepts and the development of logical thinking and problem solving skills among primary school students. Numeracy literacy extends beyond arithmetic skills to include understanding numbers, recognizing patterns and relationships, and applying mathematical concepts in everyday context. Children’s numeracy development is influenced not only by formal learning at school but also by support from the family environment, particularly parental involvement in home based learning activities. Various studies indicate that parental involvement is closely related to children’s literacy and numeracy development. Research by Solichah and Fardana (2023) reveals that parental participation in children’s literacy development remains at a low to moderate level, both at home and in school related activities. This situation highlights the need to strengthen parents roles in supporting numeracy literacy from an early age. This article aims to examine the concept of numeracy literacy among primary school students, analyze the role of parents in its development, and identify challenges and strategies for strengthening family based numeracy literacy. Using a literature review approach that draws on academic journals by lecturers of UIN Maulana Malik Ibrahim Malang and parenting and family education books, this study finds that consistent and contextual parental involvement contributeds positively to children’s numeracy literacy development .